The Improvement Of Students' Conceptual Understanding Using The Experimental Learning Method - Rahmina, Aula; Wahyuni, Agus; Zainuddin, Zainuddin; Hamid, Abdul; Musdar, Musdar (Universitas Syiah Kuala, 2024)
In Physics learning, students face challenges in the learning process if they do not grasp the fundamental concepts of physics itself. The low conceptual understanding of students is caused by the fact that the learning targets of most teachers focus solely on covering the material, rather than on how students master the material and understand physics concepts. Efforts to address this issue involve implementing the experimental learning method. This study aims to determine the improvement of students' conceptual understanding using the experimental learning method. The research employs a Pre-Experimental Design with a One Group Pretest-Posttest pattern, with a sample of 31 students from class XII MIPA 4 selected through simple random sampling. The instruments used consist of non-tests (lesson plans, worksheets, student observation sheets, and student responses) and test instruments (conceptual understanding test). Data processing techniques involve quantitative analysis and calculation of N-Gain scores. The data analysis results are grouped into three categories: Validity analysis, Practicality analysis, and Effectiveness analysis. The Validity analysis results indicate that both non-test and test instruments are valid (V). The Practicality analysis results, based on non-test instruments such as student observation sheets, show an average rating in the excellent category (SB). Meanwhile, the Effectiveness analysis results indicate that the experimental learning method falls into the high category, and student response questionnaires average a good rating. Therefore, it can be concluded that the experimental learning method can improve students' conceptual understanding, with an N-Gain score of 0.73.